UNEA-7 side event charts a path for climate-resilient land, water and food systems - CGIAR Multifunctional Landscapes (CGIAR System Organization, 2025)
Achieving climate-resilient land, water, and food systems requires stronger alignment between scientific evidence, policy processes, and implementation at scale. This article summarizes key discussions from a CGIAR-hosted side event at the seventh session of the United Nations Environment Assembly (UNEA-7), which convened researchers, policymakers, and practitioners to examine pathways for integrated and resilient environmental management. The event highlighted the role of science-based solutions, cross-sectoral coordination, and inclusive governance in addressing climate risks, ecosystem degradation, and food insecurity. Emphasis was placed on translating research into actionable policy insights and fostering partnerships that support sustainable land and water management. The article underscores the importance of global policy platforms such as UNEA in advancing evidence-informed decision-making and accelerating progress toward resilient and sustainable food systems.